2012
DOI: 10.1111/j.1502-3885.2012.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Dating of snow avalanches by means of wound‐induced vessel anomalies in sub‐arctic Betula pubescens

Abstract: Dendrogeomorphic research has long relied on scarred trees to reconstruct the frequency of mass‐movement processes. Injuries have mostly been dated macroscopically by counting the tree rings formed after wounding. Tree‐ring anatomical anomalies induced by cambial injury, in contrast, have only recently been recognized as proxy records of past events. We investigated 12 sub‐arctic downy birch (Betula pubescens Ehrh.) trees scarred by snow avalanches in Norway and Iceland. Earlywood vessel lumina were measured f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Quantification of a model's sensitivity to disturbance predictors might be also influenced by the number of available tree rings formed after the treatment, as experimental design should include not only the period immediately following the disturbance, but also several years afterwards to allow sufficient time for both adjustment and recovery. In our study, responses to most of the treatments (tilting, scarring, root exposure) are considered immediate (Hitz et al, 2008;Heinrich and Gärtner, 2008;Arbellay et al, 2013;Groover, 2016), and the graphical representation in Fig. 2 shows that our results are in agreement with this.…”
Section: Disturbance Effect On Specific Hydraulic Conductivitysupporting
confidence: 81%
See 1 more Smart Citation
“…Quantification of a model's sensitivity to disturbance predictors might be also influenced by the number of available tree rings formed after the treatment, as experimental design should include not only the period immediately following the disturbance, but also several years afterwards to allow sufficient time for both adjustment and recovery. In our study, responses to most of the treatments (tilting, scarring, root exposure) are considered immediate (Hitz et al, 2008;Heinrich and Gärtner, 2008;Arbellay et al, 2013;Groover, 2016), and the graphical representation in Fig. 2 shows that our results are in agreement with this.…”
Section: Disturbance Effect On Specific Hydraulic Conductivitysupporting
confidence: 81%
“…2 shows that our results are in agreement with this. Previous studies have found varying recovery speeds of wood anatomical parameters after strong mechanical events causing cambial damage (flood, rockfall, avalanche), ranging from 1 to 5 years (Arbellay et al, 2012b(Arbellay et al, , 2013Tumajer et al, 2015). Based on this, our experimental design included three analysed post-treatment years.…”
Section: Disturbance Effect On Specific Hydraulic Conductivitymentioning
confidence: 99%
“…George et al 2002;Ballesteros et al 2010b;Arbellay et al 2010a,b;Wertz et al 2013). Other processes, such as snow avalanches, were not studied frequently in the past (Arbellay et al 2013). Tree microscopic response to wounding was primarily studied between rings formed in the year of disturbance and subsequent years as well as in uninjured control rings (Figure 2A).…”
Section: Tracheid and Vessel Anomaliesmentioning
confidence: 99%
“…To protect itself against fungi and bacteria infestation, an injured tree will start to compartmentalize the affected wood (Shigo, 1986), form boundary zones within the bark (Biggs, 1985), and initiate the formation of anatomical changes within the xylem such as reduced tracheid or vessel lumina (Stoffel and Hitz, 2008;Arbellay et al, 2010Arbellay et al, , 2012Arbellay et al, , 2013 or the production of callus tissue (Neely, 1979(Neely, , 1988Delvaux et al, 2010)-a thin layer of undifferentiated cells as a response to injury that may help reestablish the vascular cambium after scarring (Smith and Sutherland, 2001). In the case of deep wounds, which are a common feature in trees injured by highenergy, geomorphic impacts (e.g., Dorren and Berger, 2006;Schneuwly-Bollschweiler and Schneuwly, 2012), trees will typically start to form callus as an extension of the undisturbed vascular cambium along the wound edges.…”
Section: Introductionmentioning
confidence: 99%